Περιβαλλοντικές επιπτώσεις από την διάδοση της οικιακής κομποστοποίησης - Κουρούγιαννη, Ρεβέκκα (Τμήμα Επιστήμης και Τεχνολογίας Περιβάλλοντος, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος,Τεχνολογικό πανεπιστήμιο Κύπρου, 2013)
The topic of my dissertation is the environmental effects of home composting by citizens. It is a result of scientific literature and research. The subject of the dissertation is related with municipal waste management and specifically with the organic solid wastes and the role they can play towards manageable sustainable development through environmental friendly methods such as home composting. The main aim of thesis is to assess the environmental impacts of home composting in Cyprus. In addition, the dissertation will explain what is home composting and why it is important for the society. It would be also mentioned, methods of promoting public awareness on home composting through Mass media campaigns. Thorough the study, the current adoption of home composting in Cyprus will be presented and the main technologies of home composting will be analyzed and compared. Also, the study will not only focus on the major environmental impacts for home composting but also on the impact on the environment from central composting, this will help on future evaluations and monitoring of environmental impacts from central composting systems or a combination between the two. Furthermore, the study will mention the economic and social benefits of home composting systems. Finally, methods and measures that can be taken to increase public awareness on home composting will be presented.
Keywords: Composting -- Cyprus; Waste; Environmental impact